Astrocytes Control Neuronal Excitability in the Nucleus Accumbens - Tommaso Fellin; Marcello D'Ascenzo; Philip G. Haydon (The Scientific World Journal)
Though accumulating evidence shows that the metabotropic glutamate receptor 5 (mGluR5) mediates some of the actions of extracellular glutamate after cocaine use, the cellular events underlying this action are poorly understood. In this review, we will discuss recent results showing that mGluR5 receptors are key regulators of astrocyte activity. Synaptic release of glutamate activates mGluR5 expressed in perisynaptic astrocytes and generates intense Ca2+ signaling in these cells. Ca2+ oscillations, in turn, trigger the release from astrocytes of the gliotransmitter glutamate, which modulates neuronal excitability by activating NMDA receptors. By integrating these results with the most recent evidence demonstrating the importance of astrocytes in the regulation of neuronal excitability, we propose that astrocytes are involved in mediating some of the mGluR5-dependent drug-induced behaviors.